Vibrio parahaemolyticus: a review on the pathogenesis, prevalence, and advance molecular identification techniques - Letchumanan, Vengadesh; Chan, Kok-Gan; Lee, Learn-Han (Frontiers in Microbiology, 2014)
Vibrio parahaemolyticus is a Gram-negative halophilic bacterium that is found in estuarine, marine and coastal environments. V. parahaemolyticus is the leading causal agent of human acute gastroenteritis following the consumption of raw, undercooked, or mishandled marine products. In rare cases, V. parahaemolyticus causes wound infection, ear infection or septicaemia in individuals with pre-existing medical conditions. V. parahaemolyticus has two hemolysins virulence factors that are thermostable direct hemolysin (tdh)-a pore-forming protein that contributes to the invasiveness of the bacterium in humans, and TDH-related hemolysin (trh), which plays a similar role as tdh in the disease pathogenesis. In addition, the bacterium is also encodes for adhesions and type III secretion systems (T3SS1 and T3SS2) to ensure its survival in the environment. This review aims at discussing the V. parahaemolyticus growth and characteristics, pathogenesis, prevalence and advances in molecular identification techniques.